2011
DOI: 10.1002/ejoc.201100506
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efficiency of Thiourea Catalysts by External Brønsted Acids in the Friedel–Crafts Alkylation of Indoles

Abstract: A novel study on the influence of external Brønsted acids on thiourea catalysts in the asymmetric Friedel-Crafts alkylation of indoles with nitroalkenes is reported. The final 3-substituted indole derivatives were synthesized with better results because of cooperative effects between the chiral thiourea and a Brønsted acid additive (1a·HA). The effects of diverse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 47 publications
8
40
0
Order By: Relevance
“…With D-and L-mandelic acid, no match or mismatch effect was observed and the chirality of the acid has no influence on the enantioselectivity; the same major isomer being formed (entries 4 and 5). Similar results have been found by Herrera et al 40 This fact showed that chirality was preferentially controlled by the thiourea catalyst. The additive acids only activated the thiourea moiety rather than participating itself into the transition state.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…With D-and L-mandelic acid, no match or mismatch effect was observed and the chirality of the acid has no influence on the enantioselectivity; the same major isomer being formed (entries 4 and 5). Similar results have been found by Herrera et al 40 This fact showed that chirality was preferentially controlled by the thiourea catalyst. The additive acids only activated the thiourea moiety rather than participating itself into the transition state.…”
Section: Resultssupporting
confidence: 90%
“…Recently, Herrera and co-workers reported that external Brønsted acids could enhance the efficiency of thiourea catalyst. 40 So we envisioned that higher enantioselectivity and reactivity might be achieved by using a suitable additive acids thus, we started to investigate the use of acid additives in this reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the reaction between indole and β-nitrostyrene, various catalytic systems have been proposed. These include hydrogen-bond-based compounds [11][12][13][14][15][16] such as thiourea [11,14,15,[17][18][19][20], phosphoric acid [16], silanediols [21,22], sulfamic acid [23] and 2,6-bis(amido)benzoic acid [24]; metal based compounds [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] such as Al III [25,39], Cu II [26][27][28][29][30]41], Zn II [31][32][33][34][35]40,…”
Section: Introductionmentioning
confidence: 99%
“…[20] Consistent with this proposed mode of binding, no change by 1 H NMR spectroscopy was observed when calcium methoxide and 1,3-diphenylthiourea were mixed alone in toluene-d 8 , implying that calcium is likely not activating the HBD. [21] ESI mass spectrometry revealed a mass corresponding to the catalyst–substrate complex (NHC B + enal), but no mass corresponding to any co-catalyst adducts. [18b, 22] Observation of this intermediate also suggests that the pendent silyl ether of NHC B remains silylated under the reaction conditions.…”
mentioning
confidence: 99%